Consumer Perception of GSM Service Quality by Networks’ Providers in Kaduna Metropolis: A Comparative Examination (Lapai Journal of Economics, 2019)
The Nigerian Global System for Mobile (GSM) telecommunication has witnessed rapid development in the last decade, following full deregulation and liberalization of the sector in 1999. The number of service providers as well as consumer subscription level has increased beyond imagination, thereby intensifying competition among the GSM service providers and increasing customers switching habit and defection rate among consumers. In this scenario, a defensive competitive strategy that is capable of keeping or retaining the existing GSM companies’ consumers rather than an aggressive competitive strategy that seeks to attract new customers is much more effective. A key defensive strategy is the maintenance and improvement of GSM companies’ service quality, as their satisfaction and patronage is likely to increase with perceived higher service quality. Thus, the prime objective of this study is to assess consumers’ perceived service quality of GSM networks in Kaduna metropolis. A questionnaire instrument was used to generate data from 500 respondents that were chosen using purposive sampling method. The data was subsequently analyzed using descriptive statistics. The study found that perceived service quality of the GSM operators in Kaduna metropolis was high and satisfactory. However, the perceived service of Glo network is the highest, followed by Zain and then Mtn. Hence, the study recommended that GSM operators should strive to sustain their current level of service quality in the short run, but should also strive to improve its service quality components in the long run so that customers perception of their service quality will improve from high to very high, or from satisfactory to very satisfactory.